2010
DOI: 10.1111/j.1398-9995.2010.02433.x
|View full text |Cite
|
Sign up to set email alerts
|

Standard care impact on angioedema because of hereditary C1 inhibitor deficiency: a 21-month prospective study in a cohort of 103 patients

Abstract: Our data demonstrate that tranexamic acid is not effective in the treatment of acute attacks and indicate that under the current therapeutic approach, the HAE related disability is effectively but partially reduced. Incomplete success does not appear to depend on limited efficacy of the drugs but on their limited use that can be overcome by implementing specific treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
2
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 19 publications
1
69
2
5
Order By: Relevance
“…In 15-30% of patients multiple anatomical unrelated localizations are involved (2,4). Zanichelli et al report 46%, 33% and 6.4% of the attacks to affect the extremities, the gastrointestinal tract and upper airways, respectively (5). In a Danish cohort 94.8% of the patients suffered from skin swelling, 59.7% from facial swelling and 96.1% from abdominal (mesenteric or intestinal) edemas, of which 16.9% resulted in abdominal complications (2).…”
Section: Clinical Picturementioning
confidence: 99%
“…In 15-30% of patients multiple anatomical unrelated localizations are involved (2,4). Zanichelli et al report 46%, 33% and 6.4% of the attacks to affect the extremities, the gastrointestinal tract and upper airways, respectively (5). In a Danish cohort 94.8% of the patients suffered from skin swelling, 59.7% from facial swelling and 96.1% from abdominal (mesenteric or intestinal) edemas, of which 16.9% resulted in abdominal complications (2).…”
Section: Clinical Picturementioning
confidence: 99%
“…Especially, delayed treatment of laryngeal swelling can cause death (11,13). Zanichelli et al (28) reported that the median age of the first symptoms was 12.0 years, and the corresponding median age at diagnosis was 24.3 years (29). In our survey, the median age at diagnosis of untested blood relatives was too late (41 years).…”
Section: Discussionmentioning
confidence: 54%
“…Table 2. Clinical, demographic and laboratory findings of screened untested relatives of HAE index patients morbidity and mortality, adverse events, and unnecessary surgical interventions (27,28). Especially, delayed treatment of laryngeal swelling can cause death (11,13).…”
Section: Discussionmentioning
confidence: 99%
“…Although they have few side efects involving most commonly nausea, vomiting, and diarrhea, which are dose-dependent, they are not as efective as androgens. In some earlier studies, antiibrinolytics were observed to decrease the frequency of atacks; however, in a recently published study, no differences were detected between groups with and without antiibrinolytics [59][60][61]. As a consequence, they suggested antiibrinolytics for long-term prophylaxis where plasma-derived C1-inh is not accessible and androgens are not suitable for use [55].…”
Section: -α Alkylatedmentioning
confidence: 83%